Live debugging on smartphones to assist learning of programming - Tan, Tidus Yu Feng (2015)
This project looks into designing and implementing an Android mobile application that can help novice developers to learn and master programming by bringing in the element of senses such as hearing, vision and touch to a whole new level. It allow novice developers to learn programming in a more intuitive way, which enables them to bring in their subconscious ‘sixth sense’ or gut feel. Thus, this encourage users to let their ideas run wild. The idea of learnable program is use to help enhanced the interaction between them and the programing (coding). There is a total of three main core functions namely, code editor, visualizer program executor and live code running. With the help of phone input and output actions, Learning Bubble allow users to code, visualizer and feel the program execution line by line or frame by frame. Users are also in control in the program execution. Next, live code running function allow users to code and let the phone work for them, but it is currently in beta version. Moving forward, it can be said that the Learning Bubble is successfully implemented. Further improvements can be made for future versions due to time limitations.